Status, contribution and participation of women in rural tourism in Kullu district, Himachal Pradesh - Sneh Gangwar (National Geographical Journal of India, 2025)
Women’s participation in the tourism sector of Himachal Pradesh, which began modestly in the 1920s and 1930s with roles such as portering, has gradually expanded. Today, although their representation remains limited in number, women have made notable strides by working as solo trek leaders, leading all-women trekking groups, serving as team leaders in mountain expeditions, and managing hotels, lodges, restaurants, trekking agencies, and travel companies at senior levels. Despite these advancements, the majority of women in tourism continue to occupy lower-tier positions within the organized sub-sectors of the industry. In a context where women constitute more than half of the population, a critical question arises: Can the balanced and inclusive development of the tourism sector be achieved without ensuring women’s equitable access to, and control over, the benefits of rural tourism? This brief paper seeks to explore this issue. It argues for the urgent need for pro-women tourism policies, action plans, and targeted programs that prioritize protection, support, and empowerment of women. Such initiatives are essential to elevate mountain women from marginal participation to equal status with their male counterparts in employment and entrepreneurial opportunities. Ensuring fair and just access to the benefits of rural tourism will not only contribute to their socio-economic empowerment but also foster broader structural transformation within mountain societies.